2018
DOI: 10.1523/jneurosci.0634-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Temporal Lobectomy Impairs Neural Classification of Body Emotions in Right Superior Temporal Sulcus and Reduces Emotional Enhancement in Distributed Brain Areas without Affecting Behavioral Classification

Abstract: Humans with amygdalar lesions show proportional reductions of the emotional response to facial expressions in the fusiform face area as well as deficits in emotion recognition from facial expressions. While processing of bodily expressions shares many similarities with facial expressions, there is no substantial evidence that lesions of the amygdala result in similar behavioral and neural sequelae. We combined behavioral assessment with functional neuroimaging in a group of male and female humans with unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 68 publications
3
20
1
Order By: Relevance
“…In summary, although brainstem abnormality is found to be associated with the promotion of idiopathic RBD from experimental and clinical perspectives (Scherfler et al, 2011;Hanyu et al, 2012), there are no apparent volume changes of GM in the brainstem in PD patients with RBD compared with those without RBD. Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004;Gharabaghi et al, 2006;Shah-Basak et al, 2018), narcolepsy (Joo et al, 2009;Weng et al, 2015), impaired emotion processing to support social interactions (Muller et al, 2008;Pan et al, 2015;Van de Vliet et al, 2018;Zhang et al, 2018), violent behaviors (Zhang et al, 2019), and some psychiatric disorders (Moreira et al, 2017;Zhao et al, 2017;Wang et al, 2018). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, although brainstem abnormality is found to be associated with the promotion of idiopathic RBD from experimental and clinical perspectives (Scherfler et al, 2011;Hanyu et al, 2012), there are no apparent volume changes of GM in the brainstem in PD patients with RBD compared with those without RBD. Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004;Gharabaghi et al, 2006;Shah-Basak et al, 2018), narcolepsy (Joo et al, 2009;Weng et al, 2015), impaired emotion processing to support social interactions (Muller et al, 2008;Pan et al, 2015;Van de Vliet et al, 2018;Zhang et al, 2018), violent behaviors (Zhang et al, 2019), and some psychiatric disorders (Moreira et al, 2017;Zhao et al, 2017;Wang et al, 2018). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004 ; Gharabaghi et al, 2006 ; Shah-Basak et al, 2018 ), narcolepsy (Joo et al, 2009 ; Weng et al, 2015 ), impaired emotion processing to support social interactions (Muller et al, 2008 ; Pan et al, 2015 ; Van de Vliet et al, 2018 ; Zhang et al, 2018 ), violent behaviors (Zhang et al, 2019 ), and some psychiatric disorders (Moreira et al, 2017 ; Zhao et al, 2017 ; Wang et al, 2018 ). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionmentioning
confidence: 98%
“…This contrasted with clear widespread changes in brain activation (mainly in temporal, parietal and cingulate cortex) and neural decoding (in the right posterior superior temporal sulcus) in TLS. We concluded that intact bilateral amygdalae are not necessary for successful recognition of body expressions (Van de Vliet et al., 2018). In the present study, we used the same dataset to investigate whether this preserved recognition is associated with compensatory changes in global network properties of the emotion recognition network by means of generalized psychophysiological interaction (gPPI) and graph theory.…”
Section: Introductionmentioning
confidence: 89%
“…At the behavioural level, amygdalectomy is associated with facial emotion recognition deficits (Monti & Meletti, 2015), but this is not a consistent finding (Adolphs, Tranel, Damasio, & Damasio, 1995; Fowler et al., 2006; Milesi et al., 2014). Furthermore, recognition of bodily expressions appears to be preserved following TLS (Atkinson, Heberlein, & Adolphs, 2007; Van de Vliet et al., 2018). At the neural level, inconsistent findings have also been reported regarding distant effects on emotional responses in TLS (Edmiston et al., 2013; Van de Vliet et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation